Inequality in fetal autopsy in Canada - Auger, Nathalie; Tiandrazana, Rémi- Claude; Healy-Profitós, Jessica; Costopoulos, André (Journal of health care for the poor and underserved, 2016)
Purpose. Inequality in use of fetal autopsy is poorly understood, despite the importance of autopsy in establishing the cause of stillbirth for future prevention. We examined fetal autopsy rates between linguistic minorities in Quebec, Canada, and assessed trends over three decades. Methods. Using registry data on 11,992 stillbirths from 1981–2011, we calculated fetal autopsy rates for Francophones, Anglophones, and Allophones by decade. Results. We found lower fetal autopsy rates for Allophones (54.4%) than Francophones (68.5%) and Anglophones (63.4%), but rates decreased over time for all language groups. After 2000, Allophones had 25% higher risk of non-autopsy relative to Francophones, with 8.8 fewer autopsies for every 100 stillbirths. Allophones who were not autopsied had 32% higher risk of having an undetermined cause of death. Conclusion. Inequality in use of fetal autopsy may be widespread for minorities in Canada. Efforts to decrease stillbirth in minorities may require policies to increase autopsy rates.

Newcomers and social and health pressures in Franco-Manitoban communities: Overview of avenues of research and preliminary considerations - Bahi, Boniface (Canadian Issues, 2008)
This article outlines theoretical considerations and preliminary data for a research project undertaken at the request of the research office at the Collège universitaire de Saint-Boniface in Winnipeg, with the support of the Corporation Catholique de la Santé du Manitoba. The Corporation's "Étude d'évaluation stratégique sur l'intégration des médecines alternatives à la médecine officielle (2006-2009)" seeks to build the capacities of public medical institutions in view of, among other things, socio-demographic changes caused by the arrival of newcomers. The study, now in progress, is already concerned with the potential clientele for the alternative health services that would be integrated into what is regarded as officiai medicine. Our research project, entitled "Nouveaux arrivants et pathologies émergentes en milieu franco-manitobain: Quelles exigences?" seeks to identify newcomers' implicit (unexpressed) and explicit (known) demands regarding sociocultural and health services available in the Franco-Manitoban host community. The first step involves collecting basic data on migration trends and their multidimensional implications at the community level. This article will, therefore, focus on contrasting local social and health services with the direct and indirect demands of newcomers. It will attempt to identify requirements for community, social and institutional development. The abovementioned theoretical considerations relate to the issues, objectives and approach of our research project. The preliminary data consist of information obtained from Accueil francophone and from several immigrants, such as the excerpt at the beginning of this paper.

Poids, santé générale et santé mentale : la situation de divers sous-groupes d'immigrants au Canada - Bergeron, Pascale; Auger, Nathalie; Hamel, Denis (Revue canadienne de santé publique, 2009)
Contexte Au Canada, l’immigrant récent est souvent en meilleure santé que le non-immigrant. L’état de santé des sous-groupes d’immigrants (ethniques, culturels, linguistiques) est moins bien connu. Méthode En utilisant des données de l’Enquête sur la santé dans les collectivités canadiennes 2005 (Cycle 3.1), les associations entre trois caractéristiques des immigrants (1-temps écoulé depuis l’immigration, 2-être une minorité visible, 3-parler une langue officielle) et trois indicateurs de santé (1-santé générale perçue, 2-santé mentale perçue, 3-indice de masse corporelle (IMC)) ont été modélisées à l’aide de régressions logistiques multiples pour les immigrants des régions métropolitaines de recensement de Montréal, Toronto et Vancouver. Elles ont été ajustées pour des facteurs sociodémographiques. Résultats Les immigrants récemment arrivés qui appartiennent à une minorité visible sont moins susceptibles d’avoir une mauvaise santé perçue, tant générale (RC 0,72; IC95 % 0,54–0,97) que mentale (RC 0,64; IC95 % 0,43–0,96) et un IMC≥25 (RC 0,51; IC95 % 0,43–0,61) que les non-immigrants. Ceux qui n’appartiennent pas à une minorité visible ne présentent pas ces associations. Les immigrants qui ne parlent pas une langue officielle sont plus susceptibles d’avoir une mauvaise santé générale perçue (RC 1,49; IC95 % 1,06–2,10) que les non-immigrants. À Toronto et Vancouver, les immigrants tendent à être associés à un IMC moindre que les non-immigrants alors que ce n’est pas le cas à Montréal. Conclusion Cette étude témoigne de la présence du phénomène de l’immigrant en bonne santé au Canada mais démontre qu’une grande variabilité existe entre les sous-groupes d’immigrants. Ces constats sont importants pour une planification adéquate des services aux immigrants.

Un regard sur la distribution des médecins de famille qui parlent français dans les communautés francophones de l’Ontario - Centre de recherche en santé dans les milieux ruraux et du nord (FOCUS sur la recherche [Université Laurentienne], 2013)
site internet de Focus sur la recherche: https://fr.cranhr.ca/focus

Examining the distribution of French speaking family physicians in Ontario’s Francophone communities - Centre for Rural and Northern Health Research (FOCUS on research [Laurentian University], 2013)
site internet de Research in focus: https://www.cranhr.ca/focus

Profil génétique et prévalence de la fibrose kystique dans les communautés acadiennes et francophones des Maritimes - Chappe, Frédéric; McGrath, Karla; Robinson, Walter; Chappe, Valérie (Francophone d'Amérique, 2009)
Nous évaluons ici la situation des Acadiens et des francophones des provinces maritimes (Nouvelle-Écosse, Nouveau-Brunswick, Île-du-Prince-Édouard) face à la fibrose kystique, la maladie génétique létale la plus répandue en Amérique du Nord. Nos résultats indiquent que plusieurs familles acadiennes et francophones sont touchées par cette maladie et qu’il existe un besoin de documentation et de services en français, spécifiques aux communautés acadiennes. Des disparités régionales ont été observées pour l’âge au diagnostic et le profil génétique, notamment dans les régions à majorité francophone. Cette analyse confirme le besoin d’études spécifiques sur la santé des Acadiens et des francophones des Maritimes.

Le moment Monfort dans la francophonie canadienne. - Charbonneau, François (Presses de l’Université d’Ottawa, 2024)

Accès aux services de santé en français et gouverne en réseau : différentes représentations et stratégies d'action - Collin, Stéphanie; Grenier, Gabrielle; McIntyre, Martine; Roy, Shanie (Revue Gouvernance, 2022)
Au Canada, l’enjeu de l’amélioration de l’accès aux services de santé en français, surtout dans les provinces hors Québec, s’inscrit dans des relations complexes entre différents acteurs qui poursuivent des objectifs variés. En 2008, au Nouveau-Brunswick, l’État a remplacé les huit régies régionales existantes par deux nouvelles régies, soit la Régie régionale de la santé A (Réseau de santé Vitalité) et la Régie régionale de la santé B (Réseau de santé Horizon). Plus tard, il a été établi que Vitalité fonctionnerait en français et Horizon en anglais, et que les réseaux assureraient la prestation des services de santé dans la langue officielle du choix des citoyens. Ainsi, l’objectif général de la recherche était de comprendre l’influence des dynamiques entre les acteurs d’une gouverne en réseau sur le traitement de l’enjeu que représente l’accès aux services de santé en français. Une méthode qualitative comprenant notamment des entretiens semi-directifs (n=26) a été retenue. Les résultats montrent que, d’une part, l’offre de services dans la langue du choix des citoyens, qui est conditionnée par le cadre juridique sur les droits linguistiques, pousse les acteurs à mobiliser des stratégies axées sur la qualité et la sécurité. D’autre part, l’accès révèle une dimension symbolique, puisqu’il est associé aux notions d’équité et de gouvernance. L’accès aux services de santé en français est un sujet délicat pour l’État, qui demeure en retrait par rapport à celui-ci. Afin de mieux répondre aux besoins en santé des citoyens, cet acteur doit faire émerger des liens de confiance et formuler des objectifs clairs. Mots-clés : gouverne, réseau, accès, santé, communautés francophones en situation minoritaire, langues officielles

Addressing the Shortage of Health Professionals in Official Language Minority Communities to Strengthen Retention Strategies for the Benefit of New Brunswick Francophone and Acadian Communities: Protocol for a Mixed Methods Design - Collin, Stéphanie; Johnson, Claire; Dubé, Anick; Laforest, Marie-Eve; Lauzier, Martin; Landry, Michel H.; Cormier, Manon; Sonier-Ferguson, Brigitte (JMIR Research Protocols, 2023)
Background: COVID-19 has highlighted already existing human resource gaps in health care systems. New Brunswick health care services are significantly weakened by a shortage of nurses and physicians, affecting regions where Official Language Minority Communities (OLMCs) reside. Since 2008, Vitalité Health Network (the “Network”), whose work language is French (with services delivered in both official languages, English and French), has provided health care to OLMCs in New Brunswick. The Network currently needs to fill hundreds of vacant physician and nurse positions. It is imperative to strengthen the network’s retention strategies to ensure its viability and maintain adequate health care services for OLMCs. The study is a collaborative effort between the Network (our partner) and the research team to identify and implement organizational and structural strategies to upscale retention. Objective: The aim of this study is to support one of New Brunswick health networks in identifying and implementing strategies to promote physician and registered nurse retention. More precisely, it wishes to make 4 important contributions to identify (and enhance our understanding of) the factors related to the retention of physicians and nurses within the Network; determine, based on the “Magnet Hospital” model and the “Making it Work” framework, on which aspects of the Network’s environment (internal or external) it should focus for its retention strategy; define clear and actionable practices to help the Network replenish its strength and vitality; and improve the quality of health care services to OLMCs. Methods: The sequential methodology combines quantitative and qualitative approaches based on a mixed methods design. For the quantitative part, data collected through the years by the Network will be used to take stock of vacant positions and examine turnover rates. These data will also help determine which areas have the most critical challenges and which ones have more successful approaches regarding retention. Recruitment will be made in those areas for the qualitative part of the study to conduct interviews and focus groups with different respondents, either currently employed or who have left it in the last 5 years. Results: This study was funded in February 2022. Active enrollment and data collection started in the spring of 2022. A total of 56 semistructured interviews were conducted with physicians and nurses. As of manuscript submission, qualitative data analysis is in progress and quantitative data collection is intended to end by February 2023. Summer and fall 2023 is the anticipated period to disseminate the results. Conclusions: Applying the “Magnet Hospital” model and the “Making it Work” framework outside urban settings will offer a novel outlook to the knowledge of professional resource shortages within OLMCs. Furthermore, this study will generate recommendations that could contribute to a more robust retention plan for physicians and registered nurses.

Une innovation réussie et durable au sein d’un réseau de santé, soit un hôpital et centre de santé communautaire en région rurale au Canada - Collin, Stéphanie; Michaud, Nancy; Ringuette, Claudie (Revue francophone sur la santé et les territoires, 2024)
Dans le monde, les décideurs publics tentent de trouver des arrangements structuraux pour améliorer la performance des systèmes de santé. La stratégie de régionalisation a été privilégiée depuis quelques décennies par une majorité des provinces canadiennes. Dans cet article, nous nous penchons sur les dynamiques relationnelles entre les acteurs associés à une régie régionale de la santé et leur influence sur la naissance et l’adoption d’une pratique innovante, soit un hôpital et centre de santé communautaire en région rurale. Une méthode de recherche qualitative a été retenue et la collecte de données a été effectuée par le biais d’entretiens semi-dirigés, de groupes de discussion, ainsi qu’une analyse documentaire. L’émergence et la pérennité d’une pratique innovante nécessitent une définition de la santé qui fait consensus, la présence d’entrepreneurs institutionnels et une redéfinition des rôles et responsabilités entre l’autorité centrale et les acteurs locaux. La mise en œuvre d’une gouvernance collaborative est également requise.

Améliorer l’accès des personnes âgées de Saint-Boniface et de Saint-Vital aux services de santé en français. Objectif 2 – Inventaire des services de santé disponibles en français et identification des déficits de services - De Moissac, Danielle; Ba, Halimatou; Gagné, Maryanne; Éthier, Sophie (Conseil communauté en santé du Manitoba, 2012)
Au Manitoba, des services de santé en français sont disponibles à Winnipeg, et plus précisément à Saint-Boniface et à Saint-Vital, où habite une forte concentration de francophones. L’objectif de ce deuxième volet de recherche sur l’accès des personnes âgées aux services de santé en français est de dresser un inventaire représentatif des services de santé publics, privés à but lucratif, privés à but non lucratif ou communautaires disponibles en français dans ces deux quartiers, pour ensuite identifier les déficits de services. On définit ici la disponibilité comme étant un service dont peuvent disposer les aînés et qui peut être utilisé par quiconque en fait la demande. Cet inventaire permettra de mieux connaître le nombre, le type et la nature des services existants et de déterminer si tous les services de santé et services sociaux disponibles en français sont répertoriés, soit dans l’Annuaire des services en français de la Société franco-manitobaine. Ceci est important, car une plus grande visibilité des services disponibles en français contribue grandement à leur utilisation par les aînés francophones et leurs aidants lorsque le besoin survient. De plus, l’inventaire permettra d’identifier le type et la nature des services manquants auxquels la population vieillissante pourrait avoir recours.

Améliorer l’accès des personnes âgées de Saint-Boniface et de Saint-Vital aux services de santé en français. Objectif 4 - Identification des ressources humaines bilingues et des pratiques actuelles en matière de ressources humaines - de Moissac, Danielle; Ba, Halimatou; Roch-Gagné, Margaux; Gagné, M. (Université de Saint-Boniface, 2012)
Le premier volet de l’étude globale « Améliorer l’accès des personnes âgées de Saint-Boniface et de Saint-Vital aux services de santé en français », dressait un portrait des états de santé et des besoins de services des personnes ainées de ces deux quartiers. Le deuxième volet de l’étude portant sur l’identification des services de santé disponibles en français, a permis de répertorier 106 organismes des secteurs public, communautaire, privé à but lucratif et privé à but non lucratif offrant des services de santé en français à Saint-Boniface et à Saint-Vital. Les buts du présent volet sont 1) de repérer les ressources humaines bilingues pouvant servir les aînés en français au sein de ces mêmes organismes en prenant en considération tout le continuum de soins et 2) de mieux comprendre les pratiques actuelles et les défis entourant le recrutement, l’embauche et la rétention des professionnels pouvant offrir des services en français. Plus précisément, nous tenterons de déterminer le nombre et le pourcentage de professionnels pouvant offrir des services en français, d’identifier la nature des services offerts par ces professionnels bilingues, de définir les pratiques actuelles quant au recrutement et à l’embauche de personnel bilingue et de cerner les défis quant au jumelage des besoins des aînés avec les ressources humaines bilingues disponibles. Ainsi, nous disposerons d’un portrait des ressources humaines bilingues et des pratiques actuelles en matière de ressources humaines quant aux établissements désignés bilingues ou francophones, aux établissements de soins de longue durée et aux fournisseurs de soins à domicile à Saint-Boniface et à SaintVital.

Improving St. Boniface and St. Vital seniors' access to French-language health services. Objective 4 - Identification of current bilingual human ressources and human resource practices - de Moissac, Danielle; Ba, Halimatou; Roch-Gagné, Margaux; Gagné, M. (Université de Saint-Boniface, 2012)
The first part of the comprehensive study entitled “Improving St. Boniface and St. Vital Seniors’ Access to French-language Health Services,” provided an overview of the health status and service needs of seniors in these two neighborhoods. The second part, focused on identifying available French-language health services, listed 106 public, community, private forprofit and private not-for-profit and community organizations offering Frenchlanguage services in St. Boniface and St. Vital. The goals of this fourth part of the study are to: 1) identify bilingual human resources able to serve seniors in French within these organizations across the continuum of care and 2) better understand current practices and challenges in recruiting, hiring and retaining professionals who can offer French-language services. Specifically, we will attempt to determine the number and percentage of professionals who can offer French-language services, identify the nature of services offered by these bilingual professionals, identify current practices for recruiting and hiring bilingual staff and identify the challenges in matching the needs of seniors with bilingual human resources. This will provide us with an overview of current bilingual human resources and human resource practices in designated bilingual or Francophone facilities, long-term care facilities and home care providers in St. Boniface and St. Vital.
Voir le rapport en anglais à partir de la page 36 du PDF joint.

Impact of language barriers on access to healthcare for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Healthcare management forum, 2017)
While there is strong international evidence that language barriers present obstacles to healthcare access, quality and safety, little research has been conducted on the experience of official language minorities in Canada. This multiple method research used on-line and paper-based surveys, combined with semi-structured individual interviews to explore the experience with access to care of Francophone minorities living in four Canadian provinces. The majority of Francophones surveyed reported limited access to French language services and described an environment where low importance is given to addressing language barriers within the health system. Even when services are available, the lack of services in French sometimes results in avoidance of care. Results confirm that many Francophones face similar barriers to care as other language minorities in Canada. Strategies to improve access for official language minorities are discussed.

Impact of language barriers on quality of care and patient safety for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Journal of Patient Experience, 2019)
Introduction: The risks to patient safety and quality of care faced by members of linguistic minority groups have been well-documented. However, little research has focused on the experience of official language minorities in Canada. Methods: This multiple method study (online and paper-based surveys combined with semi-structured individual interviews with patients and interpreters-health navigators) explored the experience of minority Francophones living in 4 Canadian provinces. Results: Patients and interpreters-navigators described experiences where language barriers contributed to poorer patient assessment, misdiagnosis and/or delayed treatment, incomplete understanding of patient condition and prescribed treatment, and impaired confidence in services received. Reliance on Google Translate and ad hoc, untrained interpreters are commonly reported, in spite of evidence highlighting the risks associated with such practice. Conclusion: Increased awareness that the risks of language barriers apply to official language minorities is essential.

Providers of language-appropriate health care providers are scarce: Self-declared language capabilities of the healthcare workforce in Ontario - Demers, Chantal; Bourgeault, Ivy Lynn; Leal, Andrew; Simkin, Sarah; Sweetman, Arthur

Equity, safety & health outcomes: The case for a national minimum data standard around health workforce language data in Canada - Demers, Chantale; Richard, Lise; Bourgeault, Ivy. Lynn

Pas de problème: Rapport du comité d'action sur les services de santé en langue française, 1976 - Dubois, Jacques (Ministère de la santé, Ontario, 1976)
Ce rapport est le fruit des travaux du Comité d'action sur les services de santé en langue française, institué par le ministère de la Santé de l'Ontario et officialisé par un arrêté-en-conseil approuvé en février 1975. Le titre "Pas de problème" est choisi parce que selon le comité, il "résume assez bien la réponse des resposnables de services de santé qui n'ont pas encore perçu les besoins d'un groupe linguistique minoritaire. Pas de problème. Cette simplification d'une situation pourtant très complexe dénote sans doute l'attitude que rencontre trop souvent la population française de l'Ontario." Après une brève recension d'écrits (majoritairement américains) sur les barrières linguistiques en santé, le rapport fait un état des lieux en Ontario à cette époque et énonce plus d'une centaine de recommandations.

Préparer le terrain pour la santé en français. Rapport final - Duguay, Lise; Fortin, Pierrette; Hendriks, Edouard; Losier, Barbara; Pinet, Léo-Paul; Schofield, Aurel; St-Pierre-Ellis, Lyne; Thébeau, Marcel; Thériault, Bernadette; Vienneau, Gilles (La Société Santé et Mieux-être en français du Nouveau-Brunswick, 2007)

Strategies to access health and social services for English-speaking older adults in Quebec: A qualitative case study - Ethier, Alexandra; Carrier, Annie (Canadian Social Work Review, 2023)
Considering that French is the dominant language in Quebec, that relatively few francophone providers of health and social services are able to speak English, and that English-speaking older adults (OAs) have low levels of bilingualism, anglophone OAs are more likely than their francophone peers to face language barriers when accessing health and social services. However, little is known about the strategies English-speaking OAs put into place to overcome the difficulties encountered due to language barriers when they access these services. We therefore aimed to document the strategies used by English-speaking OAs when, due to language barriers, they faced difficulties in accessing health and social services. We conducted a qualitative case study with ten English-speaking OAs in the Eastern Townships in Quebec. Through interviews and document reviews, we collected data which we then analyzed thematically. We identified seven strategies used by English-speaking OAs: investigating for health- and access-related information in English, creating their own services, entering the health and social services system offered in French, entering the health and social services system with help from others, putting the responsibility of overcoming the language barrier on the provider, splitting that responsibility, and taking on the responsibility. Our results highlight a potential burden associated with the involvement of the English-speaking community in enabling English-speaking OAs to access health and social services. Keywords: access, health services, social services, official language minority, language barriers, strategies

L'intervention du gouvernement fédéral canadien en matière de droits linguistiques dans le secteur de la santé - Farley, Roger; Guillemette, Roger; Rivest, François (2015)

Services de santé dans la langue officielle du patient : liens avec la proximité, la région et les facteurs sociodémographiques - Fernandes, Daphné (Statistique Canada, 2025)
À l’aide des données tirées de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 et de la Base de données ouverte sur les établissements de soins de santé, la présente étude examine l’incidence de la proximité des établissements de santé, et d’autres facteurs régionaux et sociodémographiques, sur l’accès à des soins dans la langue de choix de la population de langue officielle en situation minoritaire au Canada. Dans cet article, les soins en concordance linguistique se rapportent aux personnes qui reçoivent des services de santé dans la langue officielle de leur choix (français ou anglais). L’analyse porte sur les adultes de 18 ans et plus vivant dans différentes régions du Canada.

Health services in a patient’s own official language: Associations with proximity, region and sociodemographic factors - Fernandes, Daphné (Statistics Canada, 2025)
Using data from the 2022 Survey on the Official Language Minority Population and the Open Database of Healthcare Facilities, this study examines how distance to health care facilities, alongside regional and sociodemographic factors, relates to access to language-concordant care for the official language minority population in Canada. In this article, language-concordant care refers to individuals receiving health care services in their preferred official language (English or French). The analysis focuses on adults aged 18 and older living across Canada.

Repérage de quelques obstacles linguistiques et culturels des soins de santé pour les immigrants francophones de la Nouvelle-Écosse - Fontaine, Louise (Port Acadie, 2010)
Ce texte s’attarde au concept d’« immigrant francophone » appliqué au contexte de la Nouvelle-Écosse. Contrairement à ce qu’on peut imaginer à un premier niveau d’analyse, ce concept est polysémique et le sens qu’on y attribue varie selon les acteurs sociaux qui l’utilisent. Donc, afin de mieux délimiter l’objet de notre propos, nous avançons quelques éléments de définition à prendre en compte. Il s’agit d’une recherche exploratoire orientée vers la formulation de quelques pistes de réflexion, voire quelques hypothèses de travail à vérifier lors de la réalisation de futures recherches dans le domaine de la santé auprès des communautés francophones et acadiennes de la Nouvelle-Écosse. Pour étoffer notre propos, nous présentons quelques données empiriques recueillies à même le travail de terrain mené principalement dans le milieu associatif à Halifax et dans le sud-ouest de la province depuis 2003. Dans ce contexte, nous avons mené des enquêtes en procédant notamment à de l’observation participante. Nous avons aussi eu recours à des documents écrits tels que des documents gouvernementaux, des articles dans des revues spécialisées, des journaux. Les liens que nous avons établis entre des thèmes comme langue, culture et santé nous ont conduite finalement à proposer quelques questions de recherche et quelques hypothèses de travail.

Évaluation des besoins des francophones et des Acadiens de la région de Saint-Jean pour un service de navigation - Forest, Mariève (Réseau santé en français de Terre-Neuve-et-Labrador, 2019)

mobilisation collective pour une santé en français en ontario. closm santé - Forest, Mariève; Gilbert, A.; Bouchard, Louise (Le moment Monfort dans la francophonie canadienne, 2024)

L'effectivité des lois linguistiques dans le secteur de la santé - Forgues, Éric; Maillet, Stéphanie (Minorités linguistiques et société, 2024)
Cet article découle d’une étude qui problématise le concept d’effectivité des lois linguistiques. Dans cette étude, nous cherchions à mieux comprendre les dimensions juridiques, sociales, organisationnelles et psychologiques qui peuvent agir sur l’effectivité des lois linguistiques dans le secteur de la santé dans les provinces du Canada qui disposent de telles lois. Sachant que les professionnels de la santé sont en première ligne pour offrir des services en français, nous avons analysé leurs perceptions en ce qui concerne divers aspects pouvant influencer l’offre de services en français. Les résultats montrent que des différences souvent significatives s’observent entre les répondantes et les répondants anglophones et francophones et ceux qui oeuvrent dans des hôpitaux anglophones et francophones. Les résultats révèlent également que des efforts doivent se poursuivre pour atteindre une effectivité accrue, tout en offrant des pistes pour mieux orienter ces efforts. Mots-clés : effectivité des lois linguistiques, santé en français, francophonie, langue de service, minorités linguistiques

The pathway to diagnosis of dementia for Francophones living in a minority situation - Garcia, Linda J.; McCLeary, L.ynn; Emerson, Victor; Léopoldoff, Hélène; Dalziel, William; Drummond, Neil; Cohen, Carole; Koehn, Sharon; Silvius, James (The Gerontologist, 2014)
Purpose of the Study: As the prevalence of dementia increases, the pressure to make early diagnoses also increases. Although patients must be able to identify the symptoms to access appropriate services, they may not be equally accessible to all citizens in a multicultural society. Health care professionals and patients may lack a common “first language.” This study explores the experience of francophone persons with dementia (PWD) and their caregivers during the peri-diagnostic period. Design and Methods: Individual interviews were undertaken to elicit information regarding symptoms, the role of the family and friends, and the access to formal services. Seven PWD and their caregivers who spoke French as their primary language but who lived in a primarily English-speaking region completed the interviews. Results and Implications: No single symptom seemed sufficient to alert participants that dementia might be present. Participants communicated that there was a dire need to inform the public about the signs of dementia; they spoke of the role of the family physician and the importance of having a long-standing relationship with a health professional. For some, having similar personal characteristics, such as language and culture, might accentuate the strength of the relationship and facilitate the process of diagnosis.

Access to dementia services in a minority situation: The case of Francophones in Ontario [infographic] - Garcia, Linda; Chomienne, Marie-Hélène; Cadieux, M.-A.; Farmanova, E.; McCleary, L.; Molnar, F.; Agapitos, M.; Dalziel, W.; Khoury, L.; French-Merkley, V.; Joanisse, J. (2014)

Examining the geographic distribution of French-speaking physicians in Ontario - Gauthier Alain P.; Timony Patrick E.; Wenghofer, Elizabeth. F. (Canadian Family Physician, 2012)
Abstract: Objective: To determine how many physicians in Ontario express a proficiency in providing services in the French language, and to assess the geographic distribution of such physicians. Design: Population-based analysis of the 2007 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. Setting: Ontario. Participants: A total of 22688 GPs, FPs, and other specialists certified by the College of Family Physicians of Canada and the Royal College of Physicians and Surgeons of Canada who responded to the survey. Main outcome measures: First official language spoken and languages of competency to conduct practice. Results: The physician-to-patient ratio by first official language spoken is 1 physician per 138 Francophone patients in Ontario. There is 1 French-speaking GP or FP for every 297 Francophone patients, and most French-speaking physicians are located in southern Ontario (91.4%), at a ratio of 1 physician per 111 Francophone patients. The most promising French-speaking physician–to–Francophone patient ratios are found in southern Ontario (1:248 for GPs and FPs, and 1:202 for other specialists) and in urban Ontario (1:266 for GPs and FPs, and 1:209 for other specialists). Conclusion: Clearly, there is a promising number of physicians, relative to the amount of French-speaking residents in Ontario, who identified a competency in offering services in French. However, while the number of physicians who indicated a self-assessed competency to deliver health services in French is promising, it is the maldistribution of such services that is of concern. Thus, efforts must be made to attract French-speaking physicians to areas where there is the greatest demand, particularly in the northern part of the province. Résumé Objectif: Déterminer combien de médecins ontariens se disent compétents pour fournir, des services en français et vérifier la distribution géographique de ces médecins. Type d’étude: Analyse démographique du rapport de 2007 sur la réinscription annuelle à l’Ordre des médecins et chirurgiens de l’Ontario. Contexte: L’Ontario. Participants: Un total de 22 688 omnipraticiens (OP), MF et autres spécialistes diplômés du Collège des médecins de famille du Canada et du Collège royal des médecins et chirurgiens du Canada qui ont répondu à l’enquête. Principaux paramètres à l’étude: Première langue officielle parlée et langues de compétence pour la pratique. Résultats: En Ontario, le rapport médecin/patient dans le cas de la première langue officielle parlée est de 1 médecin pour 138 patients francophones. On compte un OP ou MF francophone pour 297 patients francophones et les médecins francophones sont localisés pour la plupart (91,4%) dans le sud de l’Ontario, où on observe 1 médecin pour 111 patients francophones. C’est dans le sud de l’Ontario que le rapport médecin francophone/patient francophone est le plus favorable (1/248 pour les OP et les MF, et 1/1202 pour les autres spécialistes) et dans les milieux urbains (1/266 pour les OP et les MF et 1/1209 pour les autres spécialistes). Conclusion: Il est certain qu’en Ontario, il y a un nombre encourageant de médecins qui, par rapport au nombre de résidents francophones, se sont dits compétents pour offrir des services en français. Malgré ce rapport favorable, c’est la mauvaise distribution de ces services qui est préoccupante. Il faudrait donc s’efforcer d’attirer des médecins francophones dans les régions où la demande est la plus forte, notamment dans le nord de la province.

Barriers and strategies to offering health services to French-speaking patients: Perspectives from family physicians in Northeastern Ontario - Gauthier, Alain P.; Timony, Patrick E. (Research in FOCUS on Research [Centre for rural and northern health research], 2015)
site internet de Research in focus: https://www.cranhr.ca/focus

Les obstacles et les stratégies dans les services de santé offerts aux patients francophones : perspectives des médecins de famille dans le Nord-Est de l'Ontario - Gauthier, Alain P.; Timony, Patrick E. (FOCUS sur la recherche [Centre de recherche en santé dans les milieux ruraux et du nord], 2015)
site internet de Focus sur la recherche: https://fr.cranhr.ca/focus

Strategies for improved French-language health services: Perspectives of family physicians in northeastern Ontario - Gauthier, Alain P.; Timony, Patrick E.; Serresse, Suzanne; Goodale, Natalie; Prpic, Jason (Canadian Family Physician, 2015)

Le potentiel d'offre et de demande de Services médicaux et diagnostiques dans la langue de communautés minoritaires : où se situe le français en Colombie-Britannique? - Giguère, Louis; Conway, Brian (Reflets, 2014)
Une étude comparative du potentiel de services médicaux dans les langues minoritaires de Colombie-Britannique révèle que des médecins non-francophones parlant français génèrent une retombée linguistique qui amplifie l’offre potentielle de services de santé et de services sociaux en français de façon dramatique. Ce mécanisme structurant s’appliquerait aux autres professions de la santé et des services sociaux, partout au Canada et il serait plus prononcé plus le contexte est minoritaire. Les communautés francophones doivent faire plus pour identifier, engager et outiller les professionnels et professionnelles « francophiles » et elles doivent élaborer une logique d’équité innovatrice pour dégager le potentiel d’offre de services de santé et de services sociaux en français dans un contexte multilingue. Mots-clés : CFASM, CLOSM, médecins parlant français, minorités linguistiques, équité, services d’interprétation, offre et demande

Portrait des services bilingues offerts au sein des hôpitaux canadiens. Rapport - Guignard Noël, Josée; LeBlanc, J.; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2016)

Le parcours d’intégration socioéconomique des nouveaux arrivants francophones à Ottawa : quels effets sur la santé? - Kouyé, Jean-Marie; Soulière, Marguerite (Reflets, 2018)
L’intégration socioéconomique constitue l’une des difficultés majeures auxquelles sont confrontés les immigrants, en particulier les nouveaux arrivants francophones. Dès leur arrivée à Ottawa, ces personnes diplômées ayant des expériences de travail sont confrontées au chômage et à la précarité économique. Cet article prend appui sur une recherche qualitative qui s’est intéressée aux parcours d’intégration socioéconomique et à leurs effets sur la santé de nouveaux arrivants (trois hommes et trois femmes). En se référant au cadre conceptuel des déterminants sociaux des inégalités sociales de santé (OMS, 2010), les analyses font ressortir les liens étroits entre l’expérience subjective des nouveaux arrivants francophones à Ottawa, les obstacles rencontrés en matière d’emploi, de revenu et de logement, et l’exposition de ces derniers à des conditions qui les rendent injustement plus exposés à des circonstances de vie qui affectent leur bien-être et leur santé. Par ailleurs, l’étude ouvre sur les perspectives émiques de la santé et du bien-être des participantes et participants, ce qui comporte des pistes significatives pour de futures recherches-interventions en travail social. Mots-clés : immigration francophone, intégration socioéconomique, nouvel arrivant, santé, inégalités sociales, emploi, logement, précarité, recherche qualitative

Is Francophone language status associated with diffences in the health services use of rural Nova Scotians? - Langille, Donald; Rainham, Daniel; Kisely, Steve (Canadian Journal of Public Health, 2012)
L’étude a pour objet de vérifier empiriquement la validité d’un modèle théorique qui propose un système de relations liant la construction de l’identité ethnolinguistique à la satisfaction de vie, un aspect du mieux-être psychologique, et à l’autoévaluation de sa santé. Un échantillon de 8 124 élèves du secondaire, provenant de 30 conseils scolaires francophones situés à l’extérieur du Québec, a participé à l’étude. Les résultats sont conformes au modèle fondé sur la théorie de l’autodétermination, qui stipule que lorsque la construction identitaire se fait dans un contexte d’appui à des besoins psychologiques de base, elle est reliée au mieux-être psychologique de la personne. Abstract

La première étape de la validation transculturelle des versions anglophones des tests de l'horloge et du Mini-Mental pour mesurer les capacités cognitives des Franco-Ontariens âgés de plus de 65 ans - Larocque, Sylvie; Lavoie, Anne-Marise; Omri, Nadia (Reflets, 2021)
La maladie d’Alzheimer est un syndrome neurodégénératif chronique caractérisé par un déclin cognitif et mnésique. Les personnes atteintes par cette maladie développent des affections rattachées à la langue. Il est important de faire passer des tests de dépistage dans la langue maternelle de la personne puisque l’aptitude linguistique décline avec la progression de la maladie. De manière générale, le Mini-mental et le test de l’horloge sont administrés en anglais aux francophones du nord de l’Ontario ce qui peut mener à une sous-évaluation de leurs capacités cognitives et à un diagnostic erroné. Voilà pourquoi le but de cette recherche était de développer et valider les tests psychométriques francophones administrés aux Franco-Ontariens. Le Mini-mental et le test de l’horloge ont été traduits selon la validation transculturelle de Caron (1999) et testés auprès des francophones du Grand Sudbury qui souffraient de déficits cognitifs (N=14). Aucune différence statistique (p>.05) entre les scores de la traduction franco-ontarienne du test de l’horloge et du Mini-mental comparés aux tests originaux n’a été détectée. Bien que d’autres recherches soient nécessaires, selon les auteures, ces traductions permettront d’assurer un dépistage juste de cette maladie chez les francophones âgés en situation minoritaire. Mots-clés : dépistage d’Alzheimer, Mini-mental de Folstein, test de l’horloge, traduction transculturelle

La parole aux communautés : nous sommes là! La vitalité des communautés de langues officielles en situation minoritaire. Rapport du Comité permanent des langues officielles - Lauzon, Guy (Gouvernement du Canada, Chambre des communes 39e Législature, 1er session, 2007)

Énoncé de position commune sur l’offre active des services de santé en français en Ontario - Le Regroupement des Entités de planification des services; de santé en français de l’Ontario; et; L’Alliance des Réseaux ontariens de santé en français (Regroupement des Entités de planification des services de santé en français de l’Ontario et Alliance des Réseaux Ontariens de santé en français, 2015)

Pour un système de santé en français amélioré au Nouveau-Brunswick - Leblanc, Gino (Gouvernement du Nouveau-Brunswick, 2010)

Toward an improved health system in french in New Brunswick - Leblanc, Gino (New-Brunswick Government, 2010)

Language barriers: Use of regular medical doctors by Canada's official language minorities - Ngwakongnwi, Emmanuel; Hemmelgarn, R., Brenda; Musto, Richard; King-Shier, Kathryn M.; Quan, Hude (Canadian Family Physician, 2012)

Patientèle francophone - Patrie, Mélanie; Barbeau-Rodrigue, Danielle; Morris, Vanessa (Canadian Medical Association Journal, 2024)

English-language health and social services access in Québec. Baseline data report 2015-2016 - Pocock, Joanne (Community Health and Social Services Network, 2016)

Immigration et santé. Où en sont les Francophones ? Une enquête sur l'état de santé des immigrants francophones en Colombie-Britannique - Poullos, Nichollos (RésoSanté Colombie-Britannique, 2018)

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

The impact of language on emergency department visits, hospitalizations, and lenght of stay among home care recipients - Reaume, M.; Batista, Ricardo; Rhodes, Emily; Knight, Braden; Imsirovic, Haris; Seale, Emily; Riad, Karine; Prud'homme, Denis; Tanuseputro, Peter (Medical care, 2021)
Background: Research considering the impact of language on health care utilization is limited. We conducted a population-based study to: (1) investigate the association between residents’ preferred language and hospital-based health care utilization; and (2) determine whether this association is modified by dementia, a condition which can exacerbate communication barriers. Methods: We used administrative databases to establish a retrospective cohort study of home care recipients (2015–2017) in Ontario, Canada, where the predominant language is English. Residents’ preferred language (obtained from in-person home care assessments) was coded as English (Anglophones), French (Francophones), or other (Allophones). Diagnoses of dementia were ascertained with a previously validated algorithm. We identified all emergency department (ED) visits and hospitalizations within 1 year. Results: Compared with Anglophones, Allophones had lower annual rates of ED visits (1.3 vs. 1.8; P<0.01) and hospitalizations (0.6 vs. 0.7; P<0.01), while Francophones had longer hospital stays (9.1 vs. 7.6 d per admission; P<0.01). After adjusting for potential confounders, Francophones and Allophones were less likely to visit the ED or be hospitalized than Anglophones. We found evidence of synergism between language and dementia; the average length of stay for Francophones with dementia was 25% (95% confidence interval: 1.10–1.39) longer when compared with Anglophones without dementia. Conclusions: Residents whose preferred language was not English were less frequent users of hospital-based health care services, a finding that is likely attributable to cultural factors. Francophones with dementia experienced the longest stays in hospital. This may be related to the geographic distribution of Francophones (predominantly in rural areas) or to suboptimal patient-provider communication.

Linguistic factors and COVID-19 outcomes among long-term care residents in Ontario, Canada - Reaume, Michael; Batista, Ricardo; Imsirovic, Haris; Bjerre, Lise; Kendall, Claire E.; Bouchard, Louise; Gauthier, Alain P.; Landry, Josette-Renée; Chomienne, Marie-Hélène; Muray, Mwali; Hsu, Amy; Prud'homme, Denis; et al. (BMC Geriarics, 2025)
Abstract Background The COVID-19 pandemic disproportionately affected frail individuals, especially those living in long-term care (LTC) homes. This study examined the role of linguistic factors on COVID-19 related outcomes in LTC homes. Methods We performed a population-based, retrospective cohort study of residents living in LTC homes in Ontario, Canada who were diagnosed with COVID-19 between March 31, 2020 and March 31, 2021. Resident language, obtained from LTC assessments, was used to classify residents into one of the three linguistic groups: Anglophone (English), Francophone (French), and allophone (other language). Language of the LTC home was determined using a person-time representation of the languages spoken by residents within each LTC home. We defined LTC facilities as French homes when Francophone residents contributed more than 25% of the person-days, and allophone homes when allophone residents contributed more than 50% of the person-days. Residents whose language corresponded to the language of the LTC home in which they were living were said to have received language-concordant care, while all other residents were said to have received language-discordant care. The outcomes of this study were ED visits, hospitalizations, and mortality within 90 days. Results We included a total of 26,829 LTC residents (20,315 Anglophones, 1,032 Francophones, and 5,482 allophones) living in 572 LTC homes (502 English, 28 French, 42 allophone) who were diagnosed with COVID-19. LTC residents who lived in language-discordant homes were more likely to have ED visits (adjusted HR 1.12, 95% CI 1.01–1.25) and hospitalizations (adjusted HR 1.15, 95% CI 1.02–1.29) when compared to LTC residents who lived in language-concordant homes. Residents-facility language discordance was not associated with overall mortality (adjusted HR 1.00, 95% CI 0.91–1.10) or in hospital mortality (adjusted HR 1.04, 95% CI 0.88–1.23). Conclusion Residents living in language-discordant LTC facilities experienced more ED visits and hospitalizations following diagnosis of COVID-19. The findings of this study highlight the importance of providing frail, vulnerable individuals with linguistically concordant care.

Qualité et sécurité des services de santé offerts en situation linguistique minoritaire en Ontario : investigations des données administratives de santé. - Reaume, Michael; Batista, Ricardo; Prud’homme, Denis; Tanuseputro, Peter (Minorités linguistiques et société, 2024)
Dans cet article, nous présentons une synthèse de plusieurs analyses récentes réalisées par notre groupe de recherche à partir de données administratives de santé pour mesurer la qualité et la sécurité des services de santé offerts aux francophones et allophones en Ontario, Canada. Les résultats de nos analyses démontrent que les Ontariennes et les Ontariens qui reçoivent des soins dans leur principale langue d’usage ont généralement de meilleurs résultats cliniques comparés à ceux qui reçoivent des soins dans une langue autre que leur principale langue d’usage. Ceci suggère que la qualité et la sécurité des soins offerts aux patients et aux patientes en situation de discordance linguistique pourraient être améliorées par le pairage de professionnel-patient parlant la même langue, par exemple, en référant un patient à un médecin qui parle la langue du patient, ou en s’assurant que les francophones ont accès aux services en français en milieux désignés en Ontario en vertu de la Loi sur les services en français et que les allophones puissent bénéficier de davantage de services d’interprétariat. Mots-clés : allophones, données administratives de santé, francophones, minorités de langue officielle, minorités linguistiques, qualité et sécurité des soins de santé

Impact of patient–family physician language concordance on healthcare utilisation and mortality: A retrospective cohort study of home care recipients in Ontario, Canada. - Reaume, Michael; Batista, Ricardo; Sucha, Ewa; Pugliese, Michael; Roberts, Rhiannon; Rhodes, Emily; Seale, Emily; Kendall, Claire. E.; Bjerre, Lise; Bouchard, Louise; Johnson, Sharon; Sood, Manish; et al. (BMJ Public Health, 2024)
Introduction As the world’s linguistic diversity continues to increase at an unprecedented rate, a growing proportion of patients will be at risk of experiencing language barriers in primary care settings. We sought to examine whether patient–family physician language concordance in a primary care setting is associated with lower rates of hospital-based healthcare utilisation and mortality. Methods We conducted a population-based retrospective cohort study of 497 227 home care recipients living in Ontario, Canada. Patient language was obtained from home care assessments while physician language was obtained from the College of Physicians and Surgeons of Ontario. We defined primary care as language concordant when patients and their rostered family physicians shared a mutually intelligible language, and we defined all other primary care as language discordant. The primary outcomes were Emergency Department (ED) visits, hospitalisations and death within 1 year of index home care assessment. Results Compared with non-English, non-French speakers who received language-discordant primary care, those who received language-concordant primary care experienced fewer ED visits (53.1% vs 57.5%; p<0.01), fewer hospitalisations (35.0% vs 37.6%; p<0.01) and less mortality (14.4% vs 16.6%; p<0.01) during the study period. In multivariable regression analyses, non-English, non-French speakers had lower risks of ED visits (adjusted hazard ratio [aHR] 0.91, 95% CI 0.88 to 0.94), hospitalisations (aHR 0.94, 95% CI 0.90 to 0.98) and death (aHR 0.87, 95% CI 0.82 to 0.93) when they received language-concordant primary care. For francophones, the risk of experiencing an ED visit, a hospitalisation or death was not impacted by the language of their family physician. Conclusions Patient–family physician language concordance is associated with a lower risk of adverse outcomes in non-English and non-French speakers. Optimising the delivery of language-concordant care could potentially result in significant decreases in the use of acute healthcare services and mortality at the population level.

Des services de santé en français dans un Nord en mutation. Un défi intercommunautaire - Réseau de santé en français au Nunavut (Association des Francophones du Nunavut, Santé en français au Nunavut, 2006)

Préparer le terrain. Soins de santé primaires en français dans le Sud de l'Ontario. Rapport régional - Réseau franco-santé du Sud de l'Ontario (2006)

Infographie : Pour un accueil en santé des personnes immigrantes francophones au Nunavut - état de situation - Réseau Santé en français au Nunavut (2021)

Health providers’ perceptions on language barriers in Catalonia’s public healthcare system - Rubio-Carbonero, Gema; Gil-Bardají, Anna (Revista de Llengua i Dret, 2025)
In this article, we present the results of an exploratory quantitative study on the situation of communication between healthcare staff in the Catalan public system and users with limited competence in the official languages of Catalonia. The study objective is to offer a comprehensive and empirically grounded overview of the current state of intercultural communication in the Catalan public health system, with and without the involvement of third-party mediation, as perceived by healthcare providers. Data were collected through a structured questionnaire administered to professionals engaged in direct patient care across public health centres in Catalonia, yielding a sample of 1 390 respondents. The findings underscore the high frequency and significant impact of language barriers in clinical encounters and highlight notable deficiencies in the resources currently available to address these challenges. , Aquest article presenta els resultats d’un estudi quantitatiu exploratori sobre la situació de la comunicació entre el personal sanitari del sistema públic català i els usuaris que tenen un coneixement limitat de les llengües oficials de Catalunya. L’objectiu de l’estudi és oferir una visió global i amb una base empírica de l’estat actual de la comunicació intercultural en el sistema públic de salut català –tant amb la mediació de tercers com sense– a partir de la percepció que en tenen els professionals sanitaris. Les dades es van recollir mitjançant un qüestionari estructurat administrat a professionals que treballen en l’atenció directa als pacients en centres públics de salut de Catalunya, que va permetre obtenir una mostra de 1.390 participants. Els resultats posen de manifest l’alta freqüència i el fort impacte de les barreres lingüístiques en les interaccions clíniques, així com mancances notables en els recursos disponibles actualment per afrontar aquests reptes. , Este artículo presenta los resultados de un estudio cuantitativo exploratorio sobre la situación de la comunicación entre el personal sanitario del sistema público catalán y los usuarios con un conocimiento limitado de las lenguas oficiales de Cataluña. El objetivo del estudio es ofrecer una visión global y con base empírica del estado actual de la comunicación intercultural en el sistema público de salud catalán –tanto con la mediación de terceros como sin ella– a partir de la percepción de los profesionales sanitarios. Los datos se recogieron mediante un cuestionario estructurado administrado a profesionales que trabajan en la atención directa al paciente en centros públicos de salud de Cataluña, con el que se obtuvo una muestra de 1.390 participantes. Los resultados ponen de manifiesto la elevada frecuencia y el fuerte impacto de las barreras lingüísticas en las interacciones clínicas, así como carencias notables en los recursos disponibles actualmente para afrontar tales desafíos.

Le Centre de santé de Clare : un modèle pour l'accès à des services de santé en français - Sangaré, Yalla (Reflets, 2014)

Trousse d’accompagnement pour l’examen médical du nouvel arrivant - Sanou, Baroma; Gauthier, Alain; Chomienne, Marie-Hélène; Prud'homme, D.; Kpazaï, G. (2018)
fs-ref-orig: Sanou, B., Gauthier, A., Chomienne, M.-H., Prud'homme, D. et Kpazaï, G. (2018). Trousse d’accompagnement pour l’examen médical du nouvel arrivant. Centre de recherche en santé dans les milieux ruraux et du nord, Institut du Savoir Montfort et Centre de la santé communautaire du Grand Sudbury. fs-code-orig: Sanou-2018

Évaluation de la mise en œuvre de services en français en contexte minoritaire : développement d’un questionnaire sur l’expérience des usagers - Sauvé-Schenk, K; Savard, Jacinthe; Savard, Sébastien; Prud’homme, Denis; van Kemenade, Solange; Le Callonnec, L; Pignac, S (2022)

Pratique # 4 : L’intégration de la variable linguistique dans la collecte de données (Île-du-PrinceÉdouard) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)

Pratique # 8 : Une infirmière coordonnatrice bilingue en milieu hospitalier à Halifax (IWK Health) (Nouvelle-Écosse) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2019, mise à jour 2025). Pratique # 8 : Une infirmière coordonnatrice bilingue en milieu hospitalier à Halifax (IWK Health) (Nouvelle-Écosse). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_pratiques_novatrices.html fs-code-orig: Savard-2025f

Socially responsible medical education: innovations and challenges in a minority setting - Schofield, Aurel; Bourgeois, Daniel (Medical Education, 2010)
Context Distributed medical education sites help train, recruit and retain doctors, notably in rural and isolated areas, by providing education and training in these areas and adapting their curriculum to meet the host community’s health needs. Objectives The Centre de Formation Médicale du Nouveau Brunswick (CFMNB; New Brunswick Medical Education Centre) was established by a partnership between two academic institutions, the Université de Sherbrooke (University of Sherbrooke), situated in the province of Quebec, and the Université de Moncton (University of Moncton), situated in the province of New Brunswick, in Canada. The CFMNB is specifically targeting a minority community (Acadians). Working to establish a high‐quality medical education programme, the CFMNB has also set community objectives to meet not only the health needs of this population, but also its social and economic needs. Methods This paper describes the overall objectives of this project, which are: to reduce the gap between community needs and academic institutional needs; to address ethno‐cultural and language differences in a defined minority population, and to develop collaboration between the partners involved, including government and community entities which are often perceived as operating in isolation from one another. We also describe why and how the CFMNB developed community‐focused objectives and the challenges that came with these innovations, and present lessons from the experience that may be relevant to other sites interested in the social responsibility of medical schools. Conclusions The CFMNB has produced interesting work and innovations in the field of social responsibility and has encountered many challenges. Continuing interaction between medical education, health research and health services to better address the needs of the population has been established. The information obtained by this process has been used to build a strategic plan for the CFMNB in order to ensure that it is socially responsive and has significant generalisable features.

Educating future physicians for francophone official language minority communities in Canada: a case study - Schrewe, Brett; Yeuchyk, Tatiana; El Hafid, Melanie; Nyhof-Young, Joyce (Canadian Medical Education Journal, 2023)
Résumé Contexte: Plus d’un million de Canadiens francophones vivent dans des communautés de langue officielle en situation minoritaire (CLOSM) hors Québec. L’accessibilité de soins linguistiquement appropriés aux CLOSM est limitée. Par conséquent, la qualité des services qui leur sont offerts en souffre.Le programme FrancoDoc a été créé en 2015 pour aider à combler cette lacune sur le plan de l’équité en matière de santé. Il vise à offrir aux étudiants en médecine francophones ou francophiles dont l’anglais est la principale langue d’enseignement les moyens d’améliorer leurs compétences en français médical. Cependant, on sait peu de choses sur les possibilités et les limites de cette initiative éducative. Méthodes: Notre étude qualitative instrumentale de cas unique a exploré les expériences des participants au programme FrancoDoc, tout en examinant les facteurs qui influencent la prestation de services de santé linguistiquement appropriés aux CLOSM. Nous avons mené des entrevues semi-structurées avec des étudiants en médecine de tout le Canada et nous en avons analysé le contenu thématiquement en utilisant une approche réflexive et inductive. Résultats: Quatre thèmes principaux ont été dégagés des 12entrevues réalisées: les facteurs facilitant l’apprentissage du français; les obstacles à l’apprentissage du français; les facteurs contextuels influençant la prestation de soins de santé linguistiquementappropriés; et les recommandations visant à améliorer l’enseignement en soins de santé de manière à préparer les apprenants à servir les CLOSM. Conclusions: Bien que très motivés par le programme FrancoDoc, les étudiants participants se heurtent à des obstacles comme les contraintes de temps, la programmation irrégulière des activités, le manque d’occasions d’apprentissage clinique régulier et la réticence des facultés de médecine. Or, pour remplir leurs obligations envers les CLOSM qu’elles servent, il est essentiel que les facultés de médecine reconnaissent la langue comme un déterminant social spécifique de la santé et qu’elles offrent un soutien solide aux initiatives comme le programme FrancoDoc. Abstract Background: Over one million Francophone Canadians live in official language minority communities (OLMC) outside of Québec. Availability and accessibility of linguistically appropriate care to these OLMCs is lacking, resulting in poorer quality of care. To help address this health equity gap, the FrancoDoc program was created in 2015 to identify Francophone/Francophile medical students enrolled at medical faculties that use English as their primary language of instruction and equip them with skills to increase their medical French abilities. Little is known, however, about the affordances and limitations of this educational endeavour. Methods: Our qualitative instrumental single case study explored participants’ experiences with FrancoDoc, while also examining factors shaping the delivery of linguistically appropriate healthcare services to OLMCs. We conducted semi-structured interviews with medical students from across Canada and thematically analyzed these using a reflexive, inductive approach. Results: Four main themes were derived from 12 interviews: factors facilitating French language learning; barriers to French language learning; contextual factors shaping linguistically appropriate healthcare provision; and recommendations to improve healthcare education to better prepare learners to provide care to OLMCs. Conclusions: Medical student participants are highly motivated to engage in educational activities linked to FrancoDoc. Their efforts are nonetheless frequently impeded by barriers such as time constraints, irregular event programming, lack of regular clinical learning opportunities, and lukewarm support from faculties of medicine. If medical faculties are to realize their obligations to the OLMCs that they serve, recognition of language as a specific social determinant of health and more robust institutional supports for initiatives like FrancoDoc are paramount.

Le vieillissement francophone en contexte minoritaire. Défis et opportunités - Siméon, Frantz; Couturier, Yves (Reflets, 2021)

Table : 15-10-0041-01 Frequency of health care or services obtained in the minority official language, by age group and gender, for adults in the official language minority population - Statistics Canada (Gouvernement du Canada, 2025)
Health services or care in the minority official language by age group and gender, Canada, among adults in the minority official language population who considered it important to obtain health services or care in the minority official language, 2022. Possibility to conduct more specific searches for Quebec, Canada outside Quebec, certain provinces, or certain regions.

Joint Position Statement on the Active Offer of French Language Health Services in Ontario - The Regroupement des Entités de planification des services; de santé en français de l’Ontario; and; the Alliance des Réseaux ontariens de santé en français (2015)

Rethinking the way we measure access to language-concordant health services for minority language populations: a secondary analysis of publicly available physician and population data in Ontario, Canada - Timony, Patrick E.; Belanger, Christopher; Bélizaire, Arlynn; Desilets, Antoine; Gauthier, Alain; Karunananthan, Sathya; Muray, Mwali-Nachishali; Peixoto, Cayden; Fitzsimon, Jonathan Peter; Godfrey, Leanda; Bjerre, Lise M. (BMJ Open, 2025)
Abstract Objective Providing care in a patient’s preferred language improves health outcomes and patient satisfaction. In Ontario, access to French-speaking physicians (FSPs) is estimated using FSP-to-Francophone population ratios and compared with total physician-to-total population ratios. This approach fails to consider the fact that FSPs also serve non-Francophone patients and that Francophones must compete with the entire population to access FSPs. As a result, this approach inaccurately suggests that Francophones have better access to language-concordant care than Anglophones/Allophones. We propose a novel approach to address this issue, enabling unbiased comparisons of access to language-concordant care across linguistic groups. Design This secondary analysis of publicly available data containing linguistic variables for the Ontario population (Statistics Canada, 2021 Census) and for family physicians (FPs) (College of Physicians and Surgeons of Ontario, January 2024) calculated competition-adjusted ratios and probabilities of accessing language-concordant care. Setting Ontario, Canada. Participants Census and publicly available data on FPs (ie, those providing comprehensive family medicine care to the community) and the Ontario population were obtained. Results Province-wide, the crude ratio of FSPs per 1000 Francophones was 3.46. After adjusting for competition, the ratio of FSP per 1000 population was 0.12, compared with a general physicians-per-1000 population ratio of 1.05. Anglophones/Allophones attached to a FP have a 100% probability of receiving care in English compared with an 11.4% probability for Francophones to receive care from a FSP. Expressed otherwise, Anglophones/Allophones are 8.8 times more likely to receive language-concordant care (ie, care in English) than Francophones. Conclusions Although crude physician-to-population ratios overestimate Francophones’ access to FSPs, competition-adjusted ratios and probabilities demonstrate that they are much less likely to access language-concordant care than Anglophones/Allophones. This novel approach has equity implications for health human resources planning and can be applied to other linguistic minority groups and healthcare providers.

Workload of French-speaking family physicians in Francophone rural and Northern communities in Ontario - Timony, Patrick E.; Gauthier, Alain P.; Sanou, Boroma; Wenghofer, Elizabeth. F. (Canadian Journal of Rural Medicine, 2018)
Introduction: Previous studies have shown that French-speaking family physicians (FSPs) in Ontario are less numerous in areas with high proportions of francophones. The purpose of the current study was to assess whether the degree of concordance between physicians' language of competence and the linguistic profile of the community in which they practise is associated with workload and to explore variations in this relation in rural and northern regions of the province. Methods: This was a secondary analysis of the 2013 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. We analyzed the primary practice location and language of competence of family physicians/general practitioners. We compared the practice characteristics of FSPs and non-French-speaking physicians (NFSPs) by the proportion of the francophone population, geographic location (north vs. south) and community size (urban vs. rural). Results: Data for 10 548 family physician/general practitioners were analyzed. In areas densely populated by francophones, FSPs worked more hours per week on average and had a greater mean number of patient visits than NFSPs. Non-French-speaking physicians working in areas densely populated by francophones had fewer patient visits per hour on average than FSPs. In most cases, the results were particularly accentuated in rural and northern communities. Conclusion: Our findings suggest that, compared to NFSPs, the demands placed on FSPs are disproportionately greater in communities where the need for French-language health care services is greatest and the supply of FSPs is the smallest. Our results underline the importance of properly preparing family physicians to work in areas densely populated by francophones.

Barriers to offering French language physician services in rural and Northern Ontario - Timony, Patrick E.; Gauthier, Alain P.; Serresse, Suzanne; Goodale, Natalie; Prpic, Jason (Rural and Remote Health, 2016)
Introduction: Rural and Northern Ontario francophones face many health-related challenges including poor health status, a poor supply of French-speaking physicians, and the potential for an inability or reduced ability to effectively communicate with anglophone healthcare providers. As such, it can reasonably be expected that rural and Northern Ontario francophones experience barriers when receiving care. However, the experience of physicians working in areas densely populated by francophones is largely unexplored. This paper identifies barriers experienced by French-speaking and Non-French-speaking rural and Northern Ontario physicians when serving francophone patients. Methods: A series of key informant interviews were conducted with 18 family physicians practicing in rural and urban francophone communities of Northeastern Ontario. Interviews were analyzed using a thematic analysis process. Results: Five categories of barrier were identified: (1) language discordance, (2) characteristics of francophone patients, (3) dominance of English in the medical profession, (4) lack of French-speaking medical personnel, and (5) physicians’ linguistic (in)sensitivity. Some barriers identified were unique to Non-French-speaking physicians (eg language discordance, use of interpreters, feelings of inadequacy), some were unique to French-speaking physicians (eg limited French education and resources), and some were common to both groups (eg lack of French-speaking colleagues/staff, added time commitments, and the particularities of Franco-Ontarian preferences and culture). Conclusions: Healthcare providers and decision makers may take interest in these results. Although physicians were the focus of the present article, the barriers expressed are likely experienced by other healthcare providers, and thus the lessons learned from this article extend beyond the physician workforce. Efforts must be made to offer educational opportunities for physicians and other healthcare providers working in areas densely populated by francophones; these include linguistic and cultural sensitivity training, in addition to teaching strategies for the practice of ‘active offer’ of French-language services. In sum, the present study outlines the importance of linguistic concordant communication in healthcare delivery, and describes some of the challenges faced when providing French-language services in rural and Northern Ontario. Key words: Canada, doctor–patient communication, French-language services, key informant interviews, language concordance, language discordance, Northern Ontario, Ontario francophones, physicians.

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services

Promising quantities, disappointing distribution. Investigating the presence of French-speaking physicians in Ontario’s rural francophone communities - Timony, Patrick; Gauthier, Alain; Hogenbirk, John. C.; Wenghofer, Elizabeth (Rural and Remote Health, 2013)
Introduction: Previous studies have suggested that there may be a lack of French language healthcare services in the province of Ontario. The purpose of this study was to determine if physicians in Ontario who expressed a proficiency in providing services in the French language are located in 'Francophone communities'. Method: Responses from 10 968 Ontario-based family physicians (FPs) certified by the College of Family Physicians of Canada and uncertified general practitioners (GPs) who responded to the 2007 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey were analysed and compared to the 2006 census of the population of Ontario. Main outcome measures were the number of FP/GPs categorized by their language of competency to conduct medical practice and the number of people categorized by their first official language spoken. The physician-to-population ratio was then compared for different groups of communities in Ontario categorized by the degree of francophonie of the community: strong French communities, with a Francophone population ≥25%; moderate French communities, with a Francophone population of 10-24%; and weak/no French communities, with a Francophone population <10%. Results: There are 5.6 French speaking FP/GPs for every 1000 Francophones in communities with a French population less than 10%. This ratio is considerably greater than what was found in moderate French communities (3.4 FP/GPs) and strong French (1.3 FP/GPs). Overall the lowest ratios were found in rural strong French communities both in southern and northern Ontario (0.8 FP/GPs and 0.9 FP/GPs respectively). The ratio for all of Ontario was 0.7-1.3. Conclusions: As the number of Francophones increases in a community, the availability of French-speaking FP/GPs actually decreases, particularly in rural northern Ontario. Furthermore, there is a paradoxical relationship between the potentially high number of FP/GPs in the province with French-language capabilities and the perceived deficiencies in the availability of French language medical services. Key words: family physician, Francophone community, general practitioners, health and human resources, language, physician-patient ratios, urban. Introduction

Reporting on knowledge, attitudes, and behaviours of pharmacists regarding the active offer of French language health services in Ontario: A quantitative survey study - Timony, Patrick; Leone, Arielle; Caron, Carolanne; Giguère, Pierre; Thabet, Pierre; Gauthier, Alain; Waite, Nancy M.; Landry, Christine (Canadian Pharmacists Journal / Revue des Pharmaciens du Canada, 2025)
Background: Patient–provider language discordances can negatively affect the availability, accessibility, acceptability, and quality (AAAQ) of pharmacy services as described by the AAAQ framework. With nearly 600,000 residents of Ontario identifying French as their mother tongue, the active offer (AO) of French language pharmacy services should be provided, yet little is known about pharmacists’ familiarity and use of AO. Methods: Ontario pharmacists completed an online survey measuring their knowledge, attitudes, and behaviours (KAB) regarding the AO for French language services (FLS). Demographics, including ability to converse in French, were collected. KAB AO scores were calculated and compared using descriptive and inferential statistics. Results: A total of 360 pharmacists completed the survey. The majority (65.1%) practiced in a primary care setting, 21.1% spoke French, and 71.8% lived in an area where less than 10% of the population were Francophone. Overall, AO scores were highest for attitude (3.8/5) and lowest for behaviours (2/5) and knowledge (1.8/5). Most pharmacists (62.8%) indicated an interest in AO training. Discussion: Gaps in KAB regarding AO for FLS by Ontario pharmacists resemble those observed throughout the health care system. Further training is suggested to address the lack of knowledge regarding AO, particularly its proactive nature, as well as strategies for its implementation. Conclusion: Although most participating pharmacists demonstrated gaps in AO knowledge and behaviour, many had favourable attitudes toward the importance of AO in the pharmacy setting and agreed that further training would be needed to improve their KAB. Further, the AO can address all 4 elements of the AAAQ framework.

Un modèle de création de simulation virtuelle en langue française pour le curriculum canadien du baccalauréat en sciences infirmières - Tyerman, Jane; Bailey, Liana (Revue Francophone Internationale de Recherche Infirmière, 2025)
Bien que le Canada soit un pays officiellement bilingue, il serait nécessaire d’augmenter de façon significative le nombre de ressources éducatives de bonne qualité en français, pour les étudiants en sciences infirmières. La simulation virtuelle est un outil pédagogique apprécié pour sa capacité d’être à la fois accessible, flexible et sécuritaire. Le but de cet article est de détailler le processus de création de simulations virtuelles en langue française utilisée pour le curriculum canadien du baccalauréat en sciences infirmières. Cet article propose un modèle en quatre étapes soutenant la création de simulations virtuelles en français : la rédaction/conversion, l’évaluation par les pairs, la revue finale et la publication. Le produit final est un référentiel d’outils pédagogiques permettant le renforcement de la formation des infirmières. Summary Although Canada is an officially bilingual country, there is still a need to significantly increase the number of good-quality, French-language educational resources for nursing students. Virtual simulation is a pedagogical tool that is appreciated for its ability to be accessible, flexible and safe. The aim of this article is to detail the process used to create French-language virtual simulations for the Canadian baccalaureate nursing curriculum. This article proposes a four-stage model supporting the creation of French-language virtual simulations: writing/conversion, peer review, final review, and publication. The final product is a repository of pedagogical tools to reinforce nursing education.

Barriers to and enablers of attendance at diabetic retinopathy screening experienced by immigrants to Canada from multiple cultural and linguistic minority groups - van Allen, Zack; Dogba, Maman Joyce.; Brent, Michael. H.; Bach, Catherine; Grimshaw, Jeremy. M.; Ivers, Noah. M.; Wang, Xiaoqin.; McCleary, Nicola.; Asad, Sarah.; Chorghay, Zahraa.; Hakim, Hina; Sutakovic, Olivera; et al. (Diabetic medicine, 2020)
Aim To identify barriers to/enablers of attendance at eye screening among three groups of immigrantsto Canada from cultural/linguistic minority groups living with diabetes. Methods Using a patient-oriented research approach leveraging Diabetes Action Canada's patient engagement platform, we interviewed a purposeful sample of people with type 2 diabetes who had immigrated to Canada from: Pakistan (interviews in Urdu), China (interviews in Mandarin) and French-speaking African and Caribbean nations (interviews in French). We collected and analysed data based on the Theoretical Domains Framework covering key modifiable factors that may operate as barriers to or enablers of attending eye screening. We used directed content analysis to code barrier/enabler domains. Barriers/enablers were mapped to behaviour change techniques to inform future intervention development. Results We interviewed 39 people (13 per group). Many barriers/enablers were consistent across groups, including views about harms caused by screening itself, practical appointment issues including forgetting, screening costs, wait times and making/getting to an appointment, lack of awareness about retinopathy screening, language barriers, and family and clinical support. Group-specific barriers/enablers included a preference to return to one's country of birth for screening, the impact of winter, and preferences for alternative medicine. Conclusion Our results can inform linguistic and culturally competent interventions to support immigrants living with diabetes in attending eye screening to prevent avoidable blindness.

Pratique # 23 : Navigateur francophone du système de santé (Terre-Neuve-et-Labrador) - van Kemenade, Solange; Michel, Jean Nephetaly; Savard, Jacinthe; Benoît, Josée (2021)
fs-ref-orig: van Kemenade, S., Michel, J.N., Savard, J. & Benoît, J. (2021, mise à jour 2025). Pratique # 23 : Navigateur francophone du système de santé (Terre-Neuve-et-Labrador). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https:// www.grefops.ca/repertoire_pratiques_novatrices.html fs-code-orig: van Kemenade-2025a

Language barriers to healthcare for linguistic minorities: The case of second language-specific health communication anxiety - Zhao, Yue; Segalowitz, Norman; Voloshyn, A.nastasiya; Chamoux, Estelle; Ryder, Andrew G. (Health Communication, 2021)
In this study we examined health communication anxiety (HCA) associated with language-discordant situations – that is, where people have to use their second language (L2) to communicate with health providers who are using their first language (L1). We adapted existing HCA scales in order to (1) assess L2 HCA in such situations separately for physical and mental/emotional health contexts and (2) control for potential confounds, such as HCA not related to L2 use and L2 communication anxiety not related to health, allowing us to obtain L2-specific measures of HCA. We examined the relationship between L2-specific HCA and willingness to use health services in language-discordant situations. English-speaking linguistic minority participants (N = 314) living in Québec, a predominantly French-speaking area of Canada, were recruited for online testing. The results revealed that, separately for both physical and mental/emotional health contexts, there were significant and meaningful L2-specific relations between HCA and willingness to use L2 health services – i.e., over and above general anxiety and discomfort about using an L2, and over and above general health communication anxiety. The effect was stronger for mental/emotional health contexts. The results are discussed in terms of their implications for understanding barriers to health services for linguistic minorities.